(untitled) (Global Journal of Science Frontier Research, 2019)
ur civilization continues to believe that pharaohs built the pyramids for burial purposes even after no pharaoh has ever been found in them. This article provides evidence that the pyramids were not built for burial purposes and the pharaohs were not the ones that built them. What can physics (and specifically nonlinear physics) tell us about the pyramids? Who and for what purpose built them? The physicist Dr. Alvarez first tried to measure cosmic rays in the Cheops Pyramid and failed. The arrows of his instruments were dancing left and right and he gave up [1]. For a physicist acquainted with the earth magnetic field, this means that the Cheops pyramid was built on top of magnetic anomaly. Nonlinear physics teaches that magnetic anomaly means that the pyramid was built either on top of magnetic vortex spinning clockwise and sucking energy in, or anti-vortex spinning counterclockwise and emitting energy out. Since the emitted earth energy would be released as earthquakes or volcanic activity, it seems that the pyramids were built on top of magnetic anti-vortices with the solemnly purpose to decrease the destructive power of the emitted earth energy. Thus, for a physicist acquaint with nonlinear physics, the earth magnetic anomaly means that the pyramid was probably built on top of anti-vortex emitting earth energy.